(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article explores various methods for effectively stopping bleeding in tongue injuries, ranging from simple home remedies to advanced medical interventions. By examining existing literature, we aim to provide a comprehensive overview of the current strategies available, their effectiveness, and potential areas for improvement.